Організаційно-ресурсне забезпечення механізму інноваційного управління ризиками переробних підприємств України - Посохов, Ігор Михайлович; Жадан, Юлія Володимирівна; Кабиш, Анна Юріївна; Падалка, Павло Андрійович (Аналітик, 2021)
У результаті дослідження визначено, що в сучасних умовах, дослідження організаційно-ресурсного забезпечення механізму інноваційного управління ризиками переробних підприємств є актуальною проблемою, вирішення якої дозволить забезпечити ефективне управління ризиками підприємств олійно-жирової галузі. Метою статті є дослідження та розроблення організаційно-ресурсного забезпечення механізму інноваційного управління ризиками переробних підприємств. Запропоновано організаційно-ресурсне забезпечення механізму інноваційного управління ризиками (МІУР) у системі управління підприємством олійно-жирової галузі України та аналіз його основних складових. Удосконалено науково-методичний підхід впровадження механізму інноваційного управління ризиками переробних підприємств на підставі використання організаційно-ресурсного забезпечення та містить організаційно-управлінське, кадрове, фінансове, інформаційно-аналітичне, матеріально-технічне (програмне), документаційно-правове забезпечення, що дозволить підвищити ефективність управління ризиками переробних підприємств.

Introduction. The study found that іn modern conditions, the study of organizational and resource provision of the mechanism of innovative risk management of enterprises of the oil and fat industry of Ukraine – an urgent problem, the solution of which will ensure effective risk management of enterprises of the oil and fat industry. The analysis of publications on the problems of forming the enterprise management mechanism showed that the mechanism of innovative risk management (MIRM) of oil and fat enterprises of Ukraine needs proper coverage as a necessary component of the enterprise management mechanism. Therefore, we believe that we should focus on the study of this problem. The purpose of the paper is to study and develop organizational and resource provision of the mechanism of innovative risk management of processing enterprises. Results. The organizational and resource provision of the mechanism of innovative risk management (MIRM) in the management system of the oil and fat industry of Ukraine and the analysis of its main components are offered. Issues of risk management of processing enterprises should be in the competence of highly qualified risk management specialists with professional education, practical experience in risk management in industrial enterprises and the desire for lifelong learning using both electronic corporate educational resources and training, seminars, conferences. To attract them, a system of motivation of professional risk managers should be developed, which will include material and moral incentives for risk management specialists, social programs and the provision of opportunities for lifelong learning at the expense of processing enterprises. Conclusions. Improved scientific and methodological approach to the implementation of the mechanism of innovative risk management of processing enterprises based on the use of organizational and resource support and includes organizational and managerial, personnel, financial, information-analytical, material-technical (software), documentation and legal support to improve management efficiency risks of processing enterprises.
Organizational and resource support of the mechanism of innovative risk management of enterprises of processing enterprises of Ukraine
Keywords: ризики; управління ризиками; механізм управління ризиками; організаційно-ресінноваційне управління ризиками; олійно-жирова галузь; risks; risk management; risk management mechanism; innovative risk management; oil and fat industry